Metode Pendidikan Qur’ani Dalam Surat Luqman (Analisis Maqāṣidī Melalui Tafsir Ibnu Asyur) - Ali, Zaky Mumtaz; Syaadah, Rifa Tsamrotul; Salsabila, Rahma Nayla (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
Luqman Al-Hakim is a special figure whose story is immortalized in the Al-Qur'an and his name is even used as one of the names of letters in the Al-Qur'an. One form of Luqman Al-Hakim's special qualities as described by Allah SWT in the Al-Qur'an is when he acted as a father and educator for his son. Luqman uses effective educational approaches and methods that we can use as role models for Qur'anic education methods today. This article aims to analyze what and how Qur'anic education methods are found in Luqman's teaching process towards his son as stated in Surah Luqman verses 12 to 19. This qualitative research uses a content analysis method which makes the interpretation of Al-Taḥrīr wa Al-Tanwīr Ibn Asyur's work as an object of research study. This tafsir was chosen because Ibn Assyur, apart from being known as a contemporary educational figure in Tunisia, he used a maqāṣidī tafsir approach in his tafsir work to explore the main values or objectives of the Al-Qur'an (Maqṣad) which are applicable to every condition of place and time. The main finding of this study is that in teaching his son, Luqman Al-Hakim used six teaching methods, namely: educating with a wise and loving attitude, understanding the priority scale of teaching material, using analogies in delivering the material, providing a general overview before entering. into the details of the material, attracting students' attention, and always providing rationalization for each material taught so that it is easily accepted and understood by students.